Durability of brown planthopper, Nilaparvata lugens, resistance in rice variety IR64 in greenhouse selection studies - Alam, Syed N.; Cohen, Michael B. (Wiley, 1998)
Colonies of brown planthopper, Nilaparvata lugens (Stål), established from three locations on Luzon Island, Philippines, were selected for adaptation to four rice varieties: IR22 (no major resistance genes), IR26 (Bph1 gene), IR64 (Bph1 and additional moderate resistance from minor genes), and IR72 (Bph3). In each of the first eleven generations, and the fifteenth generation, the fitness of N. lugens from subcolonies reared on each of the varieties was measured with four tests: survival to adult, feeding rate, female weight, and developmental time. In three of the four tests, insects from all three locations showed slower adaptation to IR64 than to IR22, IR26, and IR72. In the fourth test, developmental time, the rate of adaptation on IR64 and IR72 was similar, and both varieties retained a significant level of resistance after 15 generations of selection. However, as measured by survival to adult, feeding rate, and female weight, after 15 generations the fitness on IR64 of N. lugens from two locations no longer differed from those on other varieties. In these two locations, Central Luzon and IRRI, IR64 has been widely grown for 10 years. After 15 generations of selection IR64 remained resistant to insects from Banaue, an isolated location where modern resistant varieties are not grown, as measured by all four tests. Our results demonstrate that the relatively greater durability of brown planthopper resistance in IR64, which has been suspected on the basis of its performance in the field, is also evident under greenhouse conditions in the absence of natural enemies and other mortality factors.